Faster and slower posttraining recovery in futsal: Multifactorial classification of recovery profiles - Wilke, C. F.; Fernandes, F. A.; Martins, F. V. C.; Lacerda, A. M.; Nakamura, F. Y.; Wanner, S. P.; Duffield, R. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate the existence of faster vs slower recovery profiles in futsal and factors distinguishing them. Methods: 22 male futsal players were evaluated in countermovement jump, 10-m sprint, creatine kinase, total quality of recovery (TQR), and Brunel Mood Scale (fatigue and vigor) before and immediately and 3, 24, and 48 h posttraining. Hierarchical cluster analysis allocated players to different recovery profiles using the area under the curve (AUC) of the percentage differences from baseline. One-way ANOVA compared the time course of each variable and players' characteristics between clusters. Results: Three clusters were identified and labeled faster recovery (FR), slower physiological recovery (SLphy), and slower perceptual recovery (SLperc). FR presented better AUC in 10-m sprint than SLphy (P = .001) and SLperc (P = .008), as well as better TQR SLphy (P = .018) and SLperc (P = .026). SLperc showed better AUC in countermovement jump than SLphy (P = .014) but presented worse fatigue AUC than SLphy (P = .014) and FR (P = .008). AUC of creatine kinase was worse in SLphy than in FR (P = .001) and SLperc (P < .001). The SLphy players were younger than SLperc players (P = .027), whereas FR were slower 10-m sprinters than SLphy players (P = .003) and SLperc (P = .013) and tended to have higher maximal oxygen consumption than SLphy (effect size =1.13). Conclusion: Different posttraining recovery profiles exist in futsal players, possibly influenced by their physical abilities and age/experience.